Marked differences between continuous long-term and clinical snapshot examinations: is the current standard of back pain diagnostics outdated? - Schmidt, Hendrik; Shirazi-Adl, Aboulfazl; Bashkuev, Maxim; Becker, Luis Alexander; Pumberger, Matthias; Duda, Georg N.; Reitmaier, Sandra (Frontiers in Bioengineering and Biotechnology, 2024)
Current clinical examination of low back pain (LBP) patients primarily relies on static clinical examinations, which rarely represent the dynamic postures patients adopt during daily activities. To gain an overview on the dynamic kinematics-kinetics changes over a day, the lumbar back kinematics of asymptomatic individuals and LBP patients were measured over 24 hours, and the passively resisted bending and torsional moments were estimated.208 asymptomatic subjects (115 females) and 116 LBP patients (71 females) were analysed.Compared to static upright standing, the mean lumbar lordosis of asymptomatic subjects drops significantly by 21° during everyday life (p<0.01). Maximum bending moments of 44.0-50.6Nm were estimated at the L2-L3. LBP patients showed significantly lower (p<0.01) lumbar flattening during daily life of about 16°. Maximum bending moments of 27-52_Nm were found at the L3-L4. The initial static upright lumbar lordosis was significantly lower in LBP population (by 6°) resulting in almost similar average lumbar shapes during daily activities in both groups.The torsional movements were with 2.2° greatest in L1-L2 independent of sex (p=0.19) and LBP (p=0.54) with moments of 6-16_Nm.The lumbar profile and associated internal moments during daily life differ substantially from those recorded during clinical examinations. LBP patients demonstrates significantly lower lordosis at the snapshot assessment and significantly lower movement variations and internal moments during daily life. Only the dynamic long-term assessments unravelled a less flexed posture in LBP population. Apparently, such a reduced dynamic flexed posture indicates a compensatory habit for pain relief.